Automotive Industry Goes East and the Drivers of Relocation in a Highly Competitive Supply Chain: A Case Study of a Multinational Electronics Plant - Attila TURI (Communications of International Proceedings, 2021)
The goal of the paper was to improve productivity metrics at a multinational automotive industry electronics company from Timisoara, Romania to prepare for an important upcoming increase in new projects and workload. Findings contradict the tendency to think of lower costs as being the main driver of relocation and offer insights into more relevant criteria and the overall business perspectives. Data from production, megalift storage area and logistics was gathered and analyzed within a period of 4 months before and after implementing a 4 month improvement project. Redesigning layout and eliminating unproductive activities have sourced an increased process flow in all analyzed areas, production productivity (49% time savings) sourcing the biggest improvement, whereas megalift storage (6% output increase) and warehouse area (15% time savings) also achieve considerable gains. The conducted approach, results and implemented changes emphasize the importance of lean management tools, formalizing performance metrics and applying VSM within a comprehensive improvement project. Besides improving productivity metrics and achieving important time savings, other important contributions at the end of the project were improving work ergonomics, operational performance and team work amongst employees, even from different departments.
Keywords: Continuous improvement; megalift storage; performance metrics; productivity; value stream mapping